2011
DOI: 10.2165/11589190-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Can Patients Diagnosed with Schizophrenia Complete Choice-Based Conjoint Analysis Tasks?

Abstract: We found that patients diagnosed with schizophrenia can complete conjoint analysis tasks, that they base their decisions on their own preferences, and that patients make trade-offs between attributes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 29 publications
(37 reference statements)
0
35
0
Order By: Relevance
“…Schizophrenia patients are very sensitive about revealing personal information, and prior DCE work showed that such patients answer hypothetical questions about others (judgments) more easily than about themselves (preferences) (10). Formulating the questions as judgments also avoided confusion with patients' experiences and expectations about how treatments could affect their own emotional responses, encouraged objectivity, and reduced potential yeasaying bias compared with a question about what patients would choose for themselves (10,(31)(32)(33)(34). Use of the results as indicators for personal treatment decisions assumes that the respondents' judgments are a valid representation of personal preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Schizophrenia patients are very sensitive about revealing personal information, and prior DCE work showed that such patients answer hypothetical questions about others (judgments) more easily than about themselves (preferences) (10). Formulating the questions as judgments also avoided confusion with patients' experiences and expectations about how treatments could affect their own emotional responses, encouraged objectivity, and reduced potential yeasaying bias compared with a question about what patients would choose for themselves (10,(31)(32)(33)(34). Use of the results as indicators for personal treatment decisions assumes that the respondents' judgments are a valid representation of personal preference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of antipsychotic preference have demonstrated that patients, physicians, and family members collectively place greater importance on productive activity (work or school) compared with positive symptoms or social functioning and place less importance on negative symptoms and side effects (8,9). Medication side effects are of greater concern among patients and their families than among clinicians (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%
“…This use of the third person has successfully been used to prevent bias from the respondent's own experience [33,34]. An example choice task is presented in Fig.…”
Section: Development Of the Conjoint Tasksmentioning
confidence: 99%
“…Studies of schizophrenia treatment with public policy makers, consumers, families, and providers have shown that respondents value reduction of positive symptoms and improved social functioning over reduction of negative symptoms and EPS (5). Other studies have shown that medication side effects are of greater concern to patients and their families than to clinicians (6)(7)(8)(9)(10). Therefore, our research question was "Which key benefit and risk attributes of second-generation antipsychotics do physicians trade off and consider when balancing formulation and adherence as adherence changes?…”
mentioning
confidence: 99%